Pengaruh Penggunaan Model Membaca Total dan Motivasi Belajar Terhadap Keterampilan Membaca Pemahaman Siswa Sekolah Dasar - Prasnanda Bunga Rafiza; Yalvema Miaz; Neviyarni suhaili; Fitriana Fitriana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research is motivated by phenomenon happens on the pitch that students have difficulty in reading comprehension. This is evident from the low values obtained by the students in reading comprehension. This phenomenon makes researchers interested in conducting research. This study aimed to obtain information about the effects of the use of models in total reading and learning motivation towards reading comprehension skills of the sixth grade students of SDN 09 Surau Gadang Kecamatan Nanggalo Padang. This research is a quantitative research methods quasy experiment. The results showed that: (1) reading comprehension skills of students taught by reading the model total is better than reading comprehension skills of students taught by conventional methods, (2) reading comprehension skills of students who have high motivation to learn are taught using models of total reading is better than reading comprehension skills of students who have high motivation to learn are taught using conventional methods, (3) read a deep understanding of writing skills have low learning motivation taught by reading the model of total better than the reading comprehension skills of students who have low learning motivation taught by conventional methods, and (4) there is no significant interaction between the model reading with the total student motivation towards reading comprehension skills. Based on this research can be concluded that there are significant models in total reading and learning motivation towards reading comprehension skills of students in the class VI SDN 09 Surau Gadang Kecamatan Nanggalo Padang.